Formoterol for the Treatment of Chronic Obstructive Pulmonary Disease - Tashkin, Donald P (Int J Chron Obstruct Pulmon Dis, 2020)
Bronchodilators, including long-acting β(2)-agonists and long-acting muscarinic antagonists, are the mainstay for treatment of patients with chronic obstructive pulmonary disease (COPD) to prevent exacerbations or reduce symptoms. Formoterol is a highly selective and potent β(2)-agonist that relaxes airway smooth muscle to significantly improve lung function. Inhaled formoterol works within 5 minutes of administration and provides improvements in spirometry measurements over 12 hours. The lipophilicity of formoterol allows it to form a depot within the smooth muscle to provide a prolonged duration of action. Following therapeutic doses, plasma concentrations are very low or undetectable. Determination of the pharmacokinetics of formoterol following high-dose administration to healthy volunteers revealed that the drug was rapidly absorbed and excreted unchanged in the urine with a half-life of 10 hours. Inhaled formoterol, as monotherapy or in combination with other agents, is an effective and safe treatment option for patients with moderate to severe COPD. Clinical studies have demonstrated improvements in lung function and COPD symptoms, particularly dyspnea; reductions in the risk of exacerbations; and improvement in patients’ health status. The adverse event profile of inhaled formoterol is similar to that of placebo, with few adverse cardiovascular events. Formoterol is a valuable bronchodilator used in the maintenance treatment of COPD. This review describes the mechanism of action, pharmacodynamics, and pharmacokinetics of inhaled formoterol. It also reviews the results of large, randomized, controlled clinical trials that evaluated the use of formoterol as monotherapy and in combination with inhaled corticosteroids, long-acting muscarinic antagonists, and triple therapy regimens in the treatment of patients with moderate to severe COPD.